Temperature Shocks and Human Mortality in the Philippines - Intalan, Louie Aldrin M.; Takahashi, Shingo (Journal in Urban and Regional Planning, 2022)
With the advent of climate change, informed policymaking and rational climate policies for mitigation and adaptation responses are imperative. The present study contributes to the body of knowledge about climate change impacts, particularly on human health in one of the most vulnerable countries, the Philippines. Using complete records of all deaths and historical climate data from 2005 to 2011, it investigates temperature and annual mortality relationships across various subgroups of the population, as well as by causes of death. After controlling for different socio-economic indicators, our fixed-effect analysis reveals that temperature is a significant determinant of all-cause mortality, with the most prominent effect on the elderly (75 years old and above). Women suffer disproportionately, too, exhibiting stronger temperature-mortality associations than men. Cause-specific mortalities show varied responses to temperature increases. However, heart disease and malnutrition mortalities have a highly positive dependence on temperature. Thus, the study illustrates the impacts of temperature and weather variability among vulnerable groups and the prevalence of some causes of death. This study offers valuable insights to enhance social preparedness for climate change. Keywords: temperature shocks, mortality, climate change, fixed-effect model, Philippines